Avaliação do potencial de reuso agrícola do efluente de uma estação de tratamento de esgoto com alagados construídos - Giafferis, Giselda Passos [UNESP] (2014)
The study took place in a sewage treatment plant located at the actual Department of Water and Sewer in Bauru, city of Sao Paulo state. This treatment plant has an average entrance flow of 4.8 l. s-1 made by upflow anaerobic filter, followed by wetland systems constructed in parallel. . As objective of this study we evaluate the effectiveness of three systems of constructed wetlands, with three different types of plants (Lily pond, Giant papyrus and Cattail),quantify, and qualify the effluents at various stages of treatment to monitor their effectiveness and the possibility of reuse in agriculture. There was a satisfactory removal of organic matter, with a mean concentration of 36 and 39mg.l-1 at the , phases 1 and 2 of the operation, respectively. The constructed wetlands effluent nitrogen and phosphate concentrations were high throughout all the system and the removal efficiency of ammonia nitrogen was much lower than expected, then the system is functioning as secondary treatment and not as tertiary treatment. The concentrations of micro-organisms found in the final effluent were also high. Therefore, it is concluded that the results of removal efficiency of organic matter, of constructed wetland systems, meet the parameters required by legislation for effluent discharges but do not attend the parameters required for nitrogen and micro organisms. This way, these analyzed plants effluents are suitable for reuse in agriculture restricted irrigation